2009
DOI: 10.1002/eji.200939225
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the role of HLA‐DRB3 T‐cell responses: Evidence for significant expression and complementary antigen presentation

Abstract: In humans, several HLA-DRB loci (DRB1/3/4/5) encode diverse b-chains that pair with a-chains to form DR molecules on the surface of APC. While DRB1 and DRB5 have been extensively studied, the role of DRB3/4 products of DR52/DR53 haplotypes has been largely neglected. To clarify the relative expression of DRB3, we quantified DRB3 mRNA levels in comparison with DRB1 mRNA from the same haplotype in both B cells and monocytes, observing quantitatively significant DRB3 synthesis. In CD19 1 cells, DRB1*03/11/13 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
20
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 53 publications
(58 reference statements)
6
20
1
Order By: Relevance
“…The observation of an additional binding capacity of WT1 332-347 to HLA-DRB3*02:02 further underscores its suitability for immunotherapeutic use, as this HLA class II molecule is highly prevalent among Caucasians (B50%) and appears to have an important role in (tumor) antigen presentation to CD4 þ T cells. 13,14 To conclude, this study confirms the potential broad applicability of WT1 332-347 -based immunotherapy clinical trials in Caucasian subjects with AML or other WT1-expressing tumor types. Such clinical studies may be highly warranted in view of the already established positive correlation between WT1 332-347 -directed immunity and clinical response in cancer patients.…”
supporting
confidence: 73%
“…The observation of an additional binding capacity of WT1 332-347 to HLA-DRB3*02:02 further underscores its suitability for immunotherapeutic use, as this HLA class II molecule is highly prevalent among Caucasians (B50%) and appears to have an important role in (tumor) antigen presentation to CD4 þ T cells. 13,14 To conclude, this study confirms the potential broad applicability of WT1 332-347 -based immunotherapy clinical trials in Caucasian subjects with AML or other WT1-expressing tumor types. Such clinical studies may be highly warranted in view of the already established positive correlation between WT1 332-347 -directed immunity and clinical response in cancer patients.…”
supporting
confidence: 73%
“…The HLA-DRB1*03 and the DRB3* haplotype most likely appeared via gene duplication of a common DRB1* gene in that locus, and in consequence, DRB3* has been considered a secondary redundant locus (50). However, the ability of DRB3* molecules to present a distinct pattern of peptides and the existence of DRB3*-restricted T cells in peripheral blood have been demonstrated (51). Here, we found that the GDP-l-fucose synthase peptide (51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65), the only peptide stimulatory in all high-responder DRB3*02:02 patients, showed the highest predicted binding affinity to this class II molecule, suggesting DRB3*02:02-restricted T cell recognition of this peptide.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, DR52b, encoded by one of the main DRB3 alleles, is expressed by half of Caucasians. In recent years, an increasing number of studies have concentrated on alternate DR molecules, describing their structure and binding characteristics and peptide binding motifs have been defined for several of them (13,26).…”
Section: Discussionmentioning
confidence: 99%